(3JfXje hEOGQI GdHfhc (B:s (3GdSjGSGJ GdeUQajI, JMdjd GdbhGFe GdeGdjI hbjGS GGdaYGdjI, GdLhGfH GdJfXejI hGdEOGQI (B/s - (3Mfaj, YHO GdZaGQs; (3CHh bMa, YHO GdSdGe s ((3GdEScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2000)
(3GdfXGe GdeUQaj aj eUQ hJWhQg, SjGSGJ GdSjhdI hGdhOGFY, GdbQhV hGdSdajGJ, JMdjd GdbhGFe GdeGdjI ddHfhc GdJLGQjI, JNUjU GdCehGd Ydi HfhO GdJhXja ddHfc GdJLGQjs
Keywords: (3GdEOGQI GdeGdjIs; (3GdHfhcs